Expression and Clinical Value of miR-185 and miR-424 in Patients with Acute Ischemic Stroke - Guo C; Yao Y; Li Q; Gao Y; Cao H (International Journal of General Medicine, 2022)
Chunxuan Guo,1,* Yanping Yao,2,* Qi Li,1 Yuanjie Gao,1 Hongyan Cao3 1Department of Neurology, People’s Hospital of Danzhou, Danzhou, Hainan, People’s Republic of China; 2Department of Pharmacy, Suzhou Xiangcheng People’s Hospital, Suzhou, Jiangsu, People’s Republic of China; 3Department of Clinical Laboratory, Suzhou TCM Hospital Affiliated to Nanjing University of Chinese Medicine, Suzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongyan CaoDepartment of Clinical Laboratory, Suzhou TCM Hospital Affiliated to Nanjing University of Chinese Medicine, 18 Yangsu Road, Suzhou, 215006, People’s Republic of ChinaTel/Fax +8618861332277Email 81323312@qq.comBackground: To investigate the expression of serum miR-185 and miR-424 in patients with acute ischemic stroke (AIS) and their predictive value. A total of 142 patients with AIS and 50 healthy controls were enrolled.Methods: According to the modified Rankin scale (mRS) score, AIS patients were divided into the good prognosis group and the poor prognosis group. Based on the National Institutes of Health Stroke Scale (NIHSS) score, AIS patients were divided into the mild group, the moderate group, and the severe group. RT-qPCR was used to determine the expression. ROC curve and Pearson correlation analysis were adopted to predict poor prognosis and analyze the correlation between the expression and NIHSS, mRS score.Results: Compared with the control group, the expression of miR-185 and miR-424 in the AIS group was significantly higher (P< 0.01). Similarly, significantly higher expressions could be found in the poor prognosis group and the severe group (P< 0.01). The ROC curve revealed that the optimal cut-off values were 2.14 and 4.08, respectively. The area under the ROC curve (0.928, 95% CI: 0.870– 0.993) was the largest, with sensitivity and specificity of 92.0% and 85.7%. Pearson correlation analysis showed that their expression was positively correlated with NIHSS score and mRS score in AIS patients (r=0.735, 0.802, 0.796, 0.873, P< 0.01).Conclusion: There are two factors related to the up-regulated expression of serum miR-185 and miR-424, one is the severity degree of neurological impairment of patients with AIS and the other is their prognosis. These two combined indicators can contribute to predicting the prognosis of AIS patients.Keywords: acute ischemic stroke, miR-185, miR-424, prognostic evaluation